Synthesis with Improved Yield and Purity of Amitraz as an Acaricide by New Catalysts - Ahmadi, A.; Mahmoudi, A. (Asian Journal of Chemistry, 2010)
Amitraz [N-methylbis(2,4-xylyliminomethyl)amine], was synthesized in a one-step manner with improved yield and purity, by new catalysts. Lead tetraacetate and Silicon tetraacetate were used as single or mixture of them as catalysts. These compounds were added to a mixture of 2,4-dimethylaniline, triethyl ortoformate and N-methyl formamide. After distillation of ethanol and ethylformate timely during the reaction, the temperature was increased and the product was obtained. The results showed that the yield and purity in this method were higher than those in previous methods that had not used catalysts. In addition, the byproducts (ethanol and ethylformate) can be used for other purposes; hence this method is more advantageous and cost-effective.